SUSTAINABILITY REPORTING AND FIRM VALUE: SYSTEMATIC LITERATURE REVIEW - Dewi, Ni Nyoman Santi; Rustiarini, Ni Wayan (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
Sustainability reporting disclosure is a clear indication that a company is striving to meet the needs of stakeholders to enhance firm value. This study is dedicated to mapping the research on the pivotal role of sustainability disclosure in bolstering firm value in Indonesia. The research method employed is a systematic literature review (SLR), utilizing 29 articles from the period 2014-2024. The results reveal a spectrum of relationships between sustainability reporting and firm value. On one end, companies are driven by various motivations to boost investor confidence and firm value, necessitating a balance between economic, social, and environmental performance. On the other end, some companies are hesitant to publish sustainability reports, while others fail to adhere to the standards set by GRI, leading to inconsistent disclosures that do not add value to the company's worth.